IBM SISTEM INFORMASI K.I.A. DAN KB. BAGI PUSKESMAS DI KECAMATAN SEMARANG SELATAN - Eniyati, Sri; Noor Santi, Rina Candra (Proceeding Fakultas Ekonomi, 2014)
The purpose of devotion to the Community is to build an Information System Maternal and Child Health (MCII) and Family Planning (FP) in South Scmarang health Ccntcr (PLJSKESMAS). This system is called SIMKIAK B that will be used by both operators provider users and administrators for administrative activities relating to Eligible Spouse services in family planning, antenatal care, maternity and childbirth, and care of infants and toddlers. This SIM will facilitate the conduct of data collection, processing, and presentation of information or reporting with respect to the MCH-FP.lmplementalion of the method is problem solving technology that is engineered to provide a solution constraint Iced by the partners, with the stage identifier and perform problem analysis, then make the application development and implementation at the partners. After the making of the operating manual is made, then continued training to prospective operators or users SIMKIA-KB, further monitoring and evaluation and reporting activities and sosialasis.